2010
DOI: 10.1182/blood-2010-01-265405
|View full text |Cite
|
Sign up to set email alerts
|

Novel pharmacokinetic behavior of intravenous busulfan in children with thalassemia undergoing hematopoietic stem cell transplantation: a prospective evaluation of pharmacokinetic and pharmacodynamic profile with therapeutic drug monitoring

Abstract: We prospectively studied the pharmacokinetics (PK) and clinical outcomes of intravenous busulfan (Bu) in 71 children with preexisting liver damage who underwent hematopoietic stem cell transplantation for thalassemia. Intravenous Bu was administered every 6 hours as part of a conditioning regimen with PK-based dose adjustment to target a conservative area under the concentration-versus-time curve (AUC) range (900-1350 Mol*min). The first-dose Bu clearance (CL) was significantly higher than the subsequent daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 35 publications
6
95
4
Order By: Relevance
“…I.v. BU along with therapeutic dose monitoring and dose modifications was a promising strategy to reduce RRT and potentially reduce the risk of graft rejection as illustrated in the study by Gaziev et al 17 However, as demonstrated in the study by Chiesa et al 10 although this approach was effective in reducing RRT, it was not able to reduce the risk of graft rejection in patients with very high-risk thalassemia major. More recently, Anurathapan et al reported a novel approach of administration of one or two courses of immune-suppressive therapy with a combination of fludarabine and dexamethsaone one to two months before the start of conditioning and followed this up with a reduced-toxicity myeloablative conditioning regimen consisting of fludarabine, i.v.…”
Section: Challenges In Selecting the Conditioning Regimen: Reducing Gmentioning
confidence: 72%
“…I.v. BU along with therapeutic dose monitoring and dose modifications was a promising strategy to reduce RRT and potentially reduce the risk of graft rejection as illustrated in the study by Gaziev et al 17 However, as demonstrated in the study by Chiesa et al 10 although this approach was effective in reducing RRT, it was not able to reduce the risk of graft rejection in patients with very high-risk thalassemia major. More recently, Anurathapan et al reported a novel approach of administration of one or two courses of immune-suppressive therapy with a combination of fludarabine and dexamethsaone one to two months before the start of conditioning and followed this up with a reduced-toxicity myeloablative conditioning regimen consisting of fludarabine, i.v.…”
Section: Challenges In Selecting the Conditioning Regimen: Reducing Gmentioning
confidence: 72%
“…Although some studies have shown that GSTA1 genotypes influence the PK of oral and i.v. BU in both adults and children; 17,[26][27][28][29][30] others did not find this association. 15,31,32 In a small pilot study, we have shown that polymorphisms in GSTM1 might influence the PK of BU.…”
Section: Introductionmentioning
confidence: 71%
“…BU CL in individuals with combined GSTM1 and GSTT1 null genotypes, but not in individuals with GSTM1 null genotype alone, 39 whereas others reported absence of such association. 17,26,27,[30][31][32] The compensatory action of other GST isoforms to defective enzyme activity has been also demonstrated. 39 We did not find clear combined effect or interaction between GSTM1 and GSTA1 genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations